Effect of Continuous Assessment Modes on Students’ Learning Outcomes in Commerce in Senior Secondary Schools in Ibadan (2014)
Studies have shown that continuous assessment (CA) is conducted without using all requisite modes, and provision of Feedback and Remediation (FaR), rather it is conducted casually using tests alone without the provision of FaR. Also, no indepth study had addressed the combined effects of CA, Teacher-Student Relationship (TSR) and Commerce Self-Efficacy (CSE) on learning outcomes. The study, therefore, investigated the effects of CA modes (classroom based with FaR and without FaR, out-of-class based with FaR and without FaR, and classroom and out of- class based with FaR and without FaR) on students‟ achievement in and attitude to Commerce. TSR and CSE were used as moderating variables. The design was pretest-posttest control group quasi-experimental design with 7 x 3 x 3 factorial matrix. Multi-stage sampling technique was employed to select 14 schools (7 each) from the two clusters of Ibadan educational zones. From each school, an arm of SS II Commerce (intact) class was randomly selected. 12 schools (2 for each experimental group) were used and the remaining two served as control. The sample size was: 142, 118, 128, 113, 109, 107, and 129 totalling 846. Four instruments developed by the researcher: Commerce Achievement Test (r = 0.74), Commerce Self-efficacy Scale (r = 0.78), Attitude to Commerce Scale (r = 0.75) and Students‟ Perception of Teacher-Students Relationship Scale (r = 0.80) and classroom-based CA Modes Battery, out-of-class-based CA Mode Battery, and; classroom and out-of-class based CA Modes Battery were used. Four research questions and seven hypotheses were answered and tested at p< 0.05. Data were analysed using descriptive statistic and ANCOVA Main effects of treatments (CA modes) on students‟ achievement (F(6,782) = 8.33) and attitude to Commerce (F(6,782) = 30.98) were significant. The classroom and outof- class based CA modes with FaR had the highest achievement score ( = 24.66). Out-of-class based CA with (FaR) had the highest positive attitude to Commerce ( = 35.07). TSR had significant main effect on achievement (F(2,782) = 3.10) and attitude to Commerce (F(2,782) = 48.92). Students with high level TSR had the highest mean achievement score ( = 30.02) and better attitude to Commerce ( = 80.00). CSE had no significant main effect on students‟ achievement but had significant main effect on attitude to Commerce (F(2,782) = 46.69). There were significant interaction effects of treatments and TSR on students‟ achievement (F(7,782) = 2.26) and attitude to Commerce (F(7,782) = 2.79). There was no significant interaction effect of treatments and CSE on students‟ achievement but was significant on attitude to Commerce (F(7,782) = 2.40). TSE and CSE had no interaction effect on students‟ achievement but had significant interaction effect on students‟ attitude to Commerce (F(1,782) = 29.20). Treatments, TSR and CSE had no significant interaction effect on students‟ achievement and attitude to Commerce. All CA modes and TSR improved students‟ learning outcomes while CSE engendered positive attitude to Commerce only. Continuous assessment modes with FaR are effective in improving students‟ learning outcomes in Commerce. CA modes should be reflected during practice. Positive teacher-student relationship should also be encouraged.